(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
This article provides information on how to develop students’ natural literacy, apply their knowledge of the natural sciences, and develop independent, critical thinking skills. Samples of PISA assignments to develop students’ natural literacy are provided.